Actionable Data Visualization for Air Quality Data in the Istanbul Location - Mengüş, Damla; Daş, Bihter (Balkan Yayın, 2022)
Air pollution is increasing day by day due to the increasing population, urbanization, and industrial development. In our country, the amounts of pollutants in the air are recorded every day at different points. These recorded data continue to be collected in an increasing amount day by day. Information overload, which renders the data meaningless, complicates the interpretation of these data. One of the ways to solve this problem is to visualize curves and trends in measured pollution concentrations over time. In this study, using the data provided by the continuous monitoring center of the Turkey Ministry of Environment, Urbanization and Climate Change, visualization of different pollutants in the air was provided. Scatter plots, line scatter plots, and bar plots were used as data visualization. Data visualization makes it easy for non-experts to estimate air quality information from the concentration profiles displayed.
Keywords: Artificial Intelligence; Yapay Zeka